Beyond receptors and signaling: epigenetic factors in the regulation of innate immunity. Issue 3 (6th January 2015) - Mehta, Stuti; Jeffrey, Kate L
Abstract : The interaction of innate immune cells with pathogens leads to changes in gene expression that elicit our body's first line of defense against infection. Although signaling pathways and transcription factors have a central role, it is becoming increasingly clear that epigenetic factors, in the form of DNA or histone modifications, as well as noncoding RNAs, are critical for generating the necessary cell lineage as well as context‐specific gene expression in diverse innate immune cell types. Much of the epigenetic landscape is set during cellular differentiation; however, pathogens and other environmental triggers also induce changes in histone modifications that can either promote tolerance or 'train' innate immune cells for a more robust antigen‐independent secondary response. Here we review the important contribution of epigenetic factors to the initiation, maintenance and training of innate immune responses. In addition, we explore how pathogens have hijacked these mechanisms for their benefit and the potential of small molecules targeting chromatin machinery as a way to boost or subdue the innate immune response in disease. Abstract : The March 2015 issue contains a Special Feature on the epigenetic mechanisms underlying health and disease. Epigenetic modifications to chromatin influence the transcriptional status of our genes. Thus, understanding the epigenetic mechanisms that regulate immune cell fate are of great importance as they will provide insight into not only how to boost immune responses but also alter harmful ones such as autoimmunity and cancer. Immunology and Cell Biology thanks the coordinators of this Special Feature ‐ Rhys Allan ‐ for his planning and input.